Nacionalismus, multikulturalismus, sociální vyloučení a „sociálně nepřizpůsobiví“: Analýza dominantního politického diskursu v České republice (2006–2011) - Ondřej Hejnal (AntropoWebzin, 2012)
This study is concerned with dominant political discourse in the Czech Republic. This discourse is structured by the circulation of theories/discourses of multiculturalism, nationalism and social exclusion (or “social non-adaptability”). The political parties analyzed are the ODS, ČSSD, KDU-ČSL, KSČM, SZ, TOP 09, VV, Severočeši.cz, and DSSS. The author constructs equations (in the manner of G. Baumann) of particular party discourses based on a qualitative analysis of the parties’ election programmes, stenographic records of the Parliament of the Czech Republic and Dělnické listy (the main journal of the DSSS). The aims of this study are: (1) a brief introduction to the relevant theories/discourses (i.e. parts of dominant discourse), (2) a description of the social constructions of “the Others” (by means of equations) from the point of view of Czech political parties, (3) intercomparison of these constructions, and (4) a construction of the overall equation of the dominant discourse.